Microglia and astrocyte dysfunction in parkinson's disease - Tae-In Kam; Jared T. Hinkle; Ted M. Dawson; Valina L. Dawson (Neurobiology of Disease, 2020)
While glia are essential for regulating the homeostasis in the normal brain, their dysfunction contributes to neurodegeneration in many brain diseases, including Parkinson's disease (PD). Recent studies have identified that PD-associated genes are expressed in glial cells as well as neurons and have crucial roles in microglia and astrocytes. Here, we discuss the role of microglia and astrocytes dysfunction in relation to PD-linked mutations and their implications in PD pathogenesis. A better understanding of microglia and astrocyte functions in PD may provide insights into neurodegeneration and novel therapeutic approaches for PD.